Aculeate Hymenopterans as Aposematic and Mimetic Models - Willadsen, Peter C. (Frontiers in Ecology and Evolution, 2022)
Aposematism and mimicry are complex phenomena which have been studied extensively; however, much of our knowledge comes from just a few focal groups, especially butterflies. Aposematic species combine a warning signal with a secondary defense that reduces their profitability as prey. Aculeate hymenopterans are an extremely diverse lineage defined by the modification of the ovipositor into a stinger which represents a potent defense against predators. Aculeates are often brightly colored and broadly mimicked by members of other Arthropod groups including Diptera, Lepidoptera, Coleoptera, and Araneae. However, aculeates are surprisingly understudied as aposematic and mimetic model organisms. Recent studies have described novel pigments contributing to warning coloration in insects and identified changes in cis-regulatory elements as potential drivers of color pattern evolution. Many biotic and abiotic factors contribute to the evolution and maintenance of conspicuous color patterns. Predator distribution and diversity seem to influence the phenotypic diversity of aposematic velvet ants while studies on bumble bees underscore the importance of intermediate mimetic phenotypes in transition zones between putative mimicry rings. Aculeate hymenopterans are attractive models for studying sex-based intraspecific mimicry as male aculeates lack the defense conferred by the females’ stinger. In some species, evolution of male and female color patterns appears to be decoupled. Future studies on aposematic aculeates and their associated mimics hold great promise for unraveling outstanding questions about the evolution of conspicuous color patterns and the factors which determine the composition and distribution of mimetic communities.